Gamma Ray Energy Absorption Buildup Factor Computation for Human Tissues in Energy Range of Medical Radionuclides Up to 10 Mean Free Paths - Sardari, Dariush; Bashiri, Bashir; Zehtabvar, Mehrnaz; Hashemi, Shahnaz; Anvariazar, Leila (European Journal of Applied Sciences, 2024)
Gamma ray energy absorption buildup factors (EABF) have been meticulously computed for a comprehensive set of 16 human tissues, encompassing breast, lung, kidney, pancreas, liver, eye lens, thyroid, brain, ovary, heart, large intestine, blood, skin, spleen, muscle, and cortical bone. These calculations encompass photon energies inherent to prevalent radionuclides, spanning from 0.021 to 1.25 MeV, while delving into penetration depths reaching up to 10 mean free paths (mfp), all accomplished via the utilization of MCNPX2.6. The outcomes underscore the pivotal role of chemical composition of tissue in determining EABF, shedding light on the substantial influence this factor wields. Particularly noteworthy is the observation that cortical bone distinctly exhibits significantly lower EABF values compared to the other tissues under investigation. Leveraging the EABF values furnished in this study offers a powerful means of regulating dose levels for both therapeutic and diagnostic applications, contributing to the precise administration of radiation-based medical interventions.